The African Church confronting the cosmic powers - Resane, K. Thomas (Verbum et ecclesia, 2024)
This article focusses on the church in Africa, dwelling with God, empowered by the Holy Spirit to confront the cosmic powers. Using the African ‘circular’ patterns, God’s presence with his people from the Old Testament times through the New Testament, an argument is presented that the African church possesses the potency to confront the cosmic powers that impinge upon the human dignity, with intentions of breaking down the community of Christ. The circle is presented as a force building towards community cohesiveness and, therefore enhancing the communality for strength against eternal forces that are aimed to destroy the church. The secret of the victory of the community over the cosmic powers is through God’s presence with his people, communality (togetherness) of his followers, and the empowerment by the Holy Spirit. God made his presence visible through shekinah , tabernacle, miracles of provision for their needs, sacrificial rituals, temple and prophetic leadership. The article concludes that God has always opted to commune with his people, because he himself is a communal God. He is in community, the trinitarian God dwelling together with and among his people. During the uncertain times of confrontation with cosmic powers, he has been at the centre while his people are encircling him and look towards him as a centre of attraction. Intradisciplinary and interdisciplinary implications: Understanding the context of African church, confronted with cosmic powers, the church is encouraged to understand the power of the presence of God. With anthropological concept of a circle, one understand the importance of community as a way of being empowered to stand the challenges of cosmic powers.